Ecological impact of Acacia mangium Willd. invasion in secondary forests in Puchong, Selangor, Malaysia - Sheip, Younes H Solaiman (2021)
Invasive exotic species pose a serious threat to the conservation of native species, communities, and ecosystems. There are various species of economic trees that are exotic to Malaysia and among these commercial trees with invasive properties Acacia mangium. It has become increasingly clear that those exotic tree species used in the commercial and agroforestry industry can cause major problems as invaders of natural and semi-natural/disturbed ecosystems as they can become structurally dominant in terrestrial situations. This study aimed to evaluate the distribution of the spatial patterns of the population of Acacia species expanding inside degraded forests of secondary trees in Malaysia, to understand the Acacia mangium trees invasion on open sites, degraded secondary forests, and agricultural lands. The study site was divided into four regions starting from the open ground region passing through the acacia trees region, the transitional region that lies between the A. mangium region and the native forest region up to the native forest region in the study site. Each region was divided into six plots which were created in the open ground region (OG), the A. mangium region (AM), the transition region (TZ), and the native forest region (NF). A total of 24 plots were created wherein each plot was 20 x 20m in size. The study sought to compare the Physico-chemical characteristics of the soils in the four regions. Composite soil samples were obtained from each subplot at 0-15 cm depth (topsoil) and 15-30 cm depth (subsoil) from a randomly selected location within the OG, AM, TZ, and NF region respectively. The abundance, density, and frequency of trees, seedlings, and seedlings were estimated and compared in the studied regions, Quadrat data were used for the computation of analytical features such as density, frequency, and abundance. Wherein the Importance Value Index (IVI) was calculated to express the dominance and success of the biological invasion of any species. Shannon–Weiner index (H'), Concentration of dominance (Cd), Pielou’s evenness index (Jsw), and Margalef’s index of species richness (Dmg) were also calculated. Seedlings' and saplings' growth performance were evaluated and compared whereby the studied species were selected from those which grew inside the forest under the canopy of trees (shade) and outside the forest in the gaps and open ground. To determine the growth performance (total height, the diameter of the base, and counting leaves) of seedlings and saplings, they were monitored monthly for six months. The results showed that the Physico-chemical variables in the study site were not significantly different. There was a significant difference (p≤0.05) in the depth of the organic layer in the native forest region, unlike other regions the GWC in the topsoil was significantly higher compared to the subsoil. However, the Acacia trees region soils showed significantly higher total nitrogen concentration than the rest of other riggings soils. The distribution analysis of the tree species in the invaded region by A. mangium indicated the highest values of IVI than the native forest region. In terms of Margalef’s index of species richness (Dmg), Pielou’s evenness index (Jsw), and Shannon's diversity index (H') their highest values were recorded in the native forest region. In contrast, the Simpson index for the concentration of dominance (Cd) was higher in the A. mangium region. The study revealed that A. mangium had high adaptability on degraded secondary forest land. Wherein the growth performance in seedling and sapling of A. mangium showed a significant increase (p< 0.05) in open ground regions compared with the other species in the native forest region. Therefore, this study concluded that nonnative A. mangium trees have the ability to alter the soil physicochemical properties to improve their growth. It also showed that the A. mangium is a source of continuous dispersal and invasion. Moreover, A. mangium also increased at greater density and abundance compared to native trees. A. mangium could rapidly become a serious threat to the biodiversity of degraded secondary forest land in close proximity to the Acacia plantation.